Burnout and perceived social support: The mediating role of secondary traumatization in nurses vs. physicians. (30th July 2019) - Hamama, Liat; Hamama‐Raz, Yaira; Stokar, Yaffa N.; Pat‐Horenczyk, Ruth; Brom, Danny; Bron‐Harlev, Efrat
Abstract: Aims: The study aimed to examine differences between paediatric nurses and physicians regarding burnout syndrome, secondary traumatic stress (STS) and perceived social support (PSS). Background: Paediatric nurses and physicians encounter cumulative effects of treating sick and injured children and helping their families, in situations that might promote burnout and STS. Design: Cross‐sectional design. Method: Nurses ( n = 158) and physicians ( N = 76) completed self‐report questionnaires on STS, PSS and burnout. Results: Nurses and physicians had similar rates of STS and burnout but showed significant differences in PSS. Furthermore, STS mediated the association between PSS and burnout for both groups; however, the effect was stronger for nurses in comparison to physicians. Conclusion: Paediatric nurses and physicians would benefit from participating in interventions geared towards reducing STS, thus minimizing burnout. Moreover, advocating social support within the organization is needed to bolster the ability for coping with sources of stress. Impact statement: Nurses' and physicians' involvement in the physical, physiological and mental needs of their paediatric patients might lead to burnout and secondary traumatic stress (STS). However, research on social support in the context of burnout and STS among nurses and physicians is scant. Secondary traumatic stress and burnout were similar for nurses and physicians, though perceived social support (PSS) was higher for nurses. Secondary traumatic stress plays a mediating role in the association between PSS and burnout among nurses and physicians. However, the mediation effect was stronger for nurses. Policy makers would be wise to advocate institutional stress management interventions to reduce secondary traumatic and to reinforce organizational support for nurses and physicians. Abstract : 目的: 此研究旨在探讨儿科护士与医生之间关于倦怠综合征、继发性创伤压力(STS)和领悟社会支持(PSS)的差异。 背景: 儿科护士和医生会在治疗患病和受伤儿童以及帮助其家庭时遭遇累积效应, 这样的情况可能会导致倦怠和继发性创伤压力(STS)。 设计: 横断设计。 方法: 护士( n = 158)和医生( N = 76)完成关于继发性创伤压力(STS)、领悟社会支持(PSS)以及倦怠的主管报告调查表。 结果: 护士和医生有着相似的的继发性创伤压力(STS)率以及倦怠率, 但领悟社会支持(PSS)率有着显著差异。此外, 继发性创伤压力(STS)调解了两组领悟社会支持(PSS)与倦怠之间的关系。然而, 相比于医生, 继发性创伤压力(STS)对护士的影响更加显著。 结论: 儿科护士和医生将受益于参与旨在减少继发性创伤压力(STS)的干预措施, 从而最大程度地减少倦怠。此外, 非常有必要在组织内倡导社会支持, 从而增强应对压力源的能力。 影响陈述: 护士和医生与儿科患者的生理和心理需求接触可能会导致倦怠和继发性创伤压力(STS)。然而, 社会支持以及倦怠和领悟社会支持(PSS)背景下对护士和医生的研究却很少。护士和医生会面对相似的继发性创伤压力和倦怠, 不过护士的领悟社会支持(PSS)相比来说会更高。继发性创伤压力对护士和医生的领悟社会支持(PSS)和倦怠有调解作用。但是, 继发性创伤压力对护士的影响更加明显。决策者应该提倡机构压力管理干预措施, 以减少继发性创伤并加强对护士和医生的组织支持。